Hydrochemical characteristics of the Karpych lake - L. Dragan; N. Mikhailenko; T. Bersan (Ribogospodarsʹka Nauka Ukraïni, 2020)
Purpose. To assess the current hydrochemical characteristics of water in the Karpych Lake for determination of the possibilities for fish rearing.